2020
DOI: 10.1097/tp.0000000000003363
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of JC Virus Nephropathy in Kidney Transplant Recipients

Abstract: Background. The vast majority of polyomavirus nephropathy (PVN) is due to BK virus, but rare cases result from JC virus reactivation. To date, only a handful of biopsy-proven JC-PVN cases have been reported. Here, we describe the clinical and pathologic findings in 7 patients with biopsy-proven JC-PVN. Methods. Search of the pathology archives at 2 institutions found 7 cases of JC-PVN. Clinical data were extracted from the electronic medical records, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Herpesvirus infections, especially CMV infection, have also been well studied ( 27 , 29 , 30 ). The number of studies on JCV infection is also increasing ( 31 , 32 ). We also detected TTV ( 33 35 ) and parvovirus B19 ( 36 38 ), which are still relatively rare in the field of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Herpesvirus infections, especially CMV infection, have also been well studied ( 27 , 29 , 30 ). The number of studies on JCV infection is also increasing ( 31 , 32 ). We also detected TTV ( 33 35 ) and parvovirus B19 ( 36 38 ), which are still relatively rare in the field of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Boldorini et al (2003) first reported morphological evidence of lytic JC virus infection in four renal specimens from AIDS patients, supporting the hypothesis that, in immunocompromised patients, active JC viral replication can also occur in the kidney and urinary tract. JC virus-related nephropathy is now recognized as a rare cause of nephropathy in transplant recipients ( Wiegley et al, 2021 ). Ureteral and bladder involvement is more rarely reported in different types of immunosuppressed patients ( Cavallo et al, 2007 ).…”
Section: Polyomavirusmentioning
confidence: 99%
“…In a study by Lopez et al, they estimated the incidence of JCV viruria to be around 25% [33]. Wiegley et al observed that, unlike BKV infection, which occurs early post-transplantation, JCV nephropathy occurs at both early and late times after renal transplantation, and that differential diagnosis for BKV may be problematic [34].…”
Section: Jcv Reactivation From Latency and Cns Dissemination After Immunosuppressionmentioning
confidence: 99%